Analisis Rasio Profitabilitas untuk Mengetahui Kinerja Keuangan pada PT Blue Bird Tbk 2021-2024 (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the profitability ratios of PT Blue Bird Tbk during 2021-2024 to evaluate its financial performance. The method used is ratio analysis, including Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results of the analysis show that all profitability ratios have increased significantly. GPM increased from 22.24% in 2021 to 32.33% in 2024, indicating efficiency in managing production costs. NPM also increased from 0.39% to 11.8%, indicating the company's ability to maintain higher net income. In addition, ROA and ROE increased from 7.48% to 19.30% and from 9.59% to 29.12%, respectively. These findings indicate that PT Blue Bird Tbk has successfully recovered from the impact of the COVID-19 pandemic and has positive growth potential in the future